Secular changes in height, weight and body mass index in Hong Kong Children - Wang Youfa; Mak Kwok-Hang; Guldan Georgia S; Lau Joseph TF; Wong Eric MC; Li Albert M; Nelson Edmund AS; So Hung-Kwan; Fok Tai-Fai; Sung Rita YT (BMC, 2008)
Abstract Background Large population growth surveys of children and adolescents aged 6 to 18 y were undertaken in Hong Kong in 1963 and 1993. The global epidemic of obesity is a major public health concern. To monitor the impact of this epidemic in Hong Kong children and to identify secular changes in growth, a further growth survey was undertaken in 2005/6. Methods Cross-sectional height and weight measurements of 14,842 children and adolescents aged 6 to 18 y from Hong Kong's 18 districts were obtained during the 2005/6 school year. Percentile curves were constructed using LMS method and sex-specific percentile values of weight-for-age, height-for-age, and BMI-for-age were compared with those data from 1963 and 1993. Results Secular changes in height, weight and BMI were noted between 1963 and 1993 and between 1993 and 2005/6. In the latter period, greater changes were observed at younger ages, and particularly in boys. On an annual basis, the 1993-2005/6 changes were less than those during 1963-1993. Using the International Obesity Task Force cut-offs, 16.7% of children were overweight or obese in 2005/6, which was a 5.1% increase since 1993. Conclusion These data provide policy-makers with further evidence of the secular changes in child growth and the increasing obesity epidemic among Hong Kong children.